PENGUATAN ETIKA DALAM BERKOMUNIKASI PADA REMAJA DI KABUPATEN MADIUN - nurchayati, zulin (JURNAL DAYA-MAS, 2019)
Communication is a basic need inherent in humans as a social beings. So also ethics in communicating is the main capital of a person in the worl of association. Strenghtening ethics in communication is very important in adolescents because in order to grow a goog personality and generation of dignified penwrus. Counseling to strenghten communication ethics is carried out over a period of representatives of adolescents in Madiun District in 15 Subdistricts. In this material it is expected that adolescents will be able to strengthen their personal and character in communicating with others and can be used as a form of adolescent character.